Land Conflict Resolution Efforts Of The Laman Kinipan Indigenous Community In Lamandau Regency By Alliansi Indigenous Peoples Of The Archipelago (Aman) To Support National Security - Dody Mulia; Agus Adriyanto Agus; Achmed Sukendro Achmed; Pujo Widodo Pujo; Wilopo Wilopo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Issues regarding security have always been a trending topic to be discussed, especially topics concerning matters that may cause conflicts of interest. Security studies that discuss security elements continue to be developed by various stakeholders. Security within the Archipelago To achieve comprehensive national security, these elements of national security must be implemented in policy formulation. Land conflict is a threat to two elements of national security, namely human security and environmental security. The escalation of the potential threat of conflict shows a very significant increase, so it is necessary to look for a solution so that it does not develop into a vertical or horizontal conflict. This problem affects the security of human citizens and the threat of environmental damage due to destruction of forest areas due to deforestation is a form of threat to these elements of national security. This study aims to unravel the land conflict resolution efforts of the Laman Kinipan Indigenous Community in Lamandau District by the Alliance of Indigenous Peoples of the Archipelago. Qualitative research methods use a case study approach. Data collection techniques were in the form of interviews with the Indigenous Peoples Alliance of the Archipelago of Central Kalimantan, the Central Kalimantan Indonesian Forum for the Environment, and the Indigenous Territory Registration Agency as well as data collection through literature study techniques. The research shows that steps of AMAN and the Coalition of Justice for the Kinipan fighting for the liberation of indigenous peoples from various forms threats to human security, such as demanding the release of Effendi Buhing and the indigenous youth of Kinipan, and various other actions is an effort to guarantee human rights for the community Kinpan custom. This also makes indigenous peoples free from fear threat to human security.Until now, the expected form of output is recognition as a customary law community legitimized by the Regional Government Lamandau Regency, there is a decree from the Ministry of Environment Life and Forestry, and the realization of national security by the Community The adat of Laman Kinipan still cannot be felt by indigenous peoples. The output that has not been felt by the beneficiaries is Indigenous Communities The Kinipan page shows the implementation of this national security has not materialized. The conclusion is with the efforts of the Alliance of Indigenous Peoples of the Archipelago in resolution of the Laman Kinipan Land conflict with the stages of community organizing, visioning, planning, and implementation and evaluation to realize national security by being linked through elements of environmental security and human security.